From Pages to Pixels: Unveiling Student Experiences with Digital Storytelling in Extensive Reading Classes - Lailiyah, Malikhatul; Fitriana, Cinta Lia (Universitas Teuku Umar, 2024)
The implementation of technology in education holds great promise, as it can increase accessibility, personalize learning, and enhance engagement. Digital storytelling has emerged as a dynamic educational tool that leverages multimedia elements to enhance learning experiences and foster a deeper understanding of subject matter. Using qualitative approach, this study tries to explore the students’ perception on the implementation of digital storytelling as assignment output in extensive reading class. Semi-structured interviews were conducted to gather data. The participants of this study are students who took a same course, Extensive Reading class. The study's results indicated that students held positive perception regarding digital storytelling tasks. They perceived these assignments as captivating, pleasurable, and a source of creative inspiration. Students enthusiastically described the experience as creative challenges project. Importantly, this positive outlook also manifested in their commitment to the assignments, as they dedicated significant time and effort to produce meaningful digital stories, demonstrating a strong sense of devotion and pride in their accomplishments.